Vaccinations in patients with multiple sclerosis: A Delphi consensus statement - Riva, Agostino; Barcella, Valeria; Benatti, Simone V; Capobianco, Marco; Capra, Ruggero; Cinque, Paola; Comi, Giancarlo; Fasolo, Maria Michela; Franzetti, Fabio; Galli, Massimo; Gerevini, Simonetta; Meroni, Luca; et al. (Multiple sclerosis, 2021)
Patients with multiple sclerosis (MS) are at increased risk of infection. Vaccination can mitigate these risks but only if safe and effective in MS patients, including those taking disease-modifying drugs. A modified Delphi consensus process (October 2017-June 2018) was used to develop clinically relevant recommendations for making decisions about vaccinations in patients with MS. A series of statements and recommendations regarding the efficacy, safety and timing of vaccine administration in patients with MS were generated in April 2018 by a panel of experts based on a review of the published literature performed in October 2017. Recommendations include the need for an 'infectious diseases card' of each patient's infectious and immunisation history at diagnosis in order to exclude and eventually treat latent infections. We suggest the implementation of the locally recommended vaccinations, if possible at MS diagnosis, otherwise with vaccination timing tailored to the planned/current MS treatment, and yearly administration of the seasonal influenza vaccine regardless of the treatment received. Patients with MS should be vaccinated with careful consideration of risks and benefits. However, there is an urgent need for more research into vaccinations in patients with MS to guide evidence-based decision making.